Deep learning‐based assessment of body composition and liver tumour burden for survival modelling in advanced colorectal cancer. Issue 1 (21st December 2022) - Keyl, Julius; Hosch, René; Berger, Aaron; Ester, Oliver; Greiner, Tobias; Bogner, Simon; Treckmann, Jürgen; Ting, Saskia; Schumacher, Brigitte; Albers, David; Markus, Peter; Wiesweg, Marcel; et al.
Abstract: Background: Personalized therapy planning remains a significant challenge in advanced colorectal cancer care, despite extensive research on prognostic and predictive markers. A strong correlation of sarcopenia or overall body composition and survival has been described. Here, we explore whether automated assessment of body composition and liver metastases from standard of care CT images can add to clinical parameters in personalized survival risk prognostication. Methods: We retrospectively analysed clinical imaging data from 85 patients (50.6% female, mean age 58.9 SD 12.2 years) with colorectal cancer and synchronous liver metastases. Pretrained deep learning models were used to assess body composition and liver metastasis geometry from abdominal CT images before the initiation of systemic treatment. Abdominal muscle‐to‐bone ratio (MBR) was calculated by dividing abdominal muscle volume by abdominal bone volume. MBR was compared with body mass index (BMI), abdominal muscle volume, and abdominal muscle volume divided by height squared. Differences in overall survival based on body composition and liver metastasis parameters were compared using Kaplan–Meier survival curves. Results were correlated with clinical and biomarker data to develop a machine learning model for survival risk prognostication. Results: The MBR, unlike abdominal muscle volume or BMI, was significantly associated with overall survival (HR 0.39, 95% CI: 0.19–0.80, P  = 0.009). The MBR ( P  = 0.022), liver metastasis surface area ( P  = 0.01) and primary tumour sidedness ( P  = 0.007) were independently associated with overall survival in multivariate analysis. Body composition parameters did not correlate with KRAS mutational status or primary tumour sidedness. A prediction model based on MBR, liver metastasis surface area and primary tumour sidedness achieved a concordance index of 0.69. Conclusions: Automated segmentation enables to extract prognostic parameters from routine imaging data for personalized survival modelling in advanced colorectal cancer patients.